No-till agriculture and the deception of sustainability in Brazil - Andrew Ofstehage; Ryan Nehring (International Journal of Agricultural Sustainability, 2021)
Agronomists and policy makers have proposed no-tillage practice and advocacy in the tropical savannah (Cerrado) of Brazil as a model for agriculture elsewhere. Building from intensive research with Embrapa and ethnographic research with two communities of transnational soy farmers, this paper explores the origins of no-tillage farming in the state of Paraná and the adoption and exploitation of no-tillage by large-scale farmers in the Cerrado of Brazil’s center-west. The spread of no-till was made possible by farmer innovation in Paraná, scientific research adapting the practice to the tropics, and and heavy application of chemical herbicides to control weeds without manual cultivation and intense soil fertility amendments in order to make the Cerrado productive for industrial agriculture. Small-scale Mennonites in the state of Goiás adopted it as an emergency measure to save their land base and compete with neighboring Brazilian farmers; large-scale family farmers from the U.S. adopted no-till to save on labor expense and reduce their liability in the face of labor laws. This indicates that while no-till in Brazil reduces soil erosion and is not a problem in itself, it emerges from a context of socio-technical fixes and its implementation supports farm profitability and agricultural expansion in the Cerrado.